Pengaruh Kesejahteraan Psikologis dan Iklim Organisasi terhadap Kepuasan Kerja - Mirsal Frans Doloksaribu; M Rajab Lubis; Nadra Ideyani (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The aimed of this research is to determine the effect of psychological wellbeing and climate organization with job satisfaction among the employees of Unit Kerja Satuan Kerja Pelaksanaan Jalan Nasional Wilayah III Provinsi Sumatera Utara. The problem is focused on the psychological wellbeing and climate organization by the company. Measuring tool use is psychological wellbeing scale, climate organization scale, and job satisfaction scale to 90 employees of Unit Kerja Satuan Kerja Pelaksanaan Jalan Nasional Wilayah III Provinsi Sumatera Utara and conducting quantitative data analysis with multiple linier regression method. The results obtained that there is a significant positive influence of psychological wellbeing and climate organization with job satisfaction. Thus it can be concluded that is an influence of psychological wellbeing and climate organization on employee job satisfaction. Psychological wellbeing  and climate organization to job satisfaction as much as 88.90% this means there are still 11.10% other factors that can affect Job satisfaction.